The determination of Erosion Rate on Andepts Soil Using Corn and Bench Terrace With USLE Methods and Small Plots in Kwala Bekala Estate University of North Sumatera - Rian Hidayat Lubis; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2015)
The way to prevent the soil erosion is using vegetation method (plants) and mechanical method (terrace). This study was aimed to determine tolerable erosion rate and Erosion Hazard Level (TBE) on Andepts soil using corn and bench terrace (inward) with slope of 9%, in April-July 2014 in the District of Kwala Bekala using small plots and USLE predictions. The results showed that the amount of erosion using small plots for control land was 1,79 ton/(ha.year), on corn land was 1,67 ton/(ha.year), and on bench terrace (inward) land was 0,44 ton/(ha.year), respectively with low Erosion Hasard Level (TBE) category. USLE predictions based on 10 years of rainfall data for control land was 49,34 ton/(ha.year), on corn land was 31,34 ton/(ha.year), and on bench terrace (inward) was 17,27 ton/(ha.year) with Erosion Hazard Level (TBE) category of low to moderate. Prediction based on the USLE for 4 months rainfall data for control land was 6,28 ton/(ha.year), on corn land was 4,003 ton/(ha.year), and on bench terrace (inward) land was 2,19 ton/(ha.year) with low Erosion Hazard Level (TBE) category. The amount of tolerable erosion rate was 29 tons/(ha.years). Keywords: Andepts Soil, Bench Terrace (inward), Corn, Erosion,